Dysphagia and disrupted cranial nerve development in a mouse model of DiGeorge (22q11) deletion syndrome - Beverly A. Karpinski; Thomas M. Maynard; Matthew S. Fralish; Samer Nuwayhid; Irene E. Zohn; Sally A. Moody; Anthony-S. LaMantia (The Company of Biologists, 2014)
We assessed feeding-related developmental anomalies in the LgDel mouse model of chromosome 22q11 deletion syndrome (22q11DS), a common developmental disorder that frequently includes perinatal dysphagia - debilitating feeding, swallowing and nutrition difficulties from birth onward - within its phenotypic spectrum. LgDel pups gain significantly less weight during the first postnatal weeks, and have several signs of respiratory infections due to food aspiration. Most 22q11 genes are expressed in anlagen of craniofacial and brainstem regions critical for feeding and swallowing, and diminished expression in LgDel embryos apparently compromises development of these regions. Palate and jaw anomalies indicate divergent oro-facial morphogenesis. Altered expression and patterning of hindbrain transcriptional regulators, especially those related to retinoic acid (RA) signaling, prefigures these disruptions. Subsequently, gene expression, axon growth and sensory ganglion formation in the trigeminal (V), glossopharyngeal (IX) or vagus (X) cranial nerves (CNs) that innervate targets essential for feeding, swallowing and digestion are disrupted. Posterior CN IX and X ganglia anomalies primarily reflect diminished dosage of the 22q11DS candidate gene Tbx1. Genetic modification of RA signaling in LgDel embryos rescues the anterior CN V phenotype and returns expression levels or pattern of RA-sensitive genes to those in wild-type embryos. Thus, diminished 22q11 gene dosage, including but not limited to Tbx1, disrupts oro-facial and CN development by modifying RA-modulated anterior-posterior hindbrain differentiation. These disruptions likely contribute to dysphagia in infants and young children with 22q11DS.